Luiz Carlos Prestes e Olga Benario: construções identitárias através da história e da literatura - Pontes, Matheus de Mesquita e (2008)
To talk about the constructed images of Luiz Carlos Prestes and Olga Benario is the main reason of this research. The biographies O Cavaleiro da Esperança: a vida de Luiz Carlos Prestes, written by Jorge Amado and Olga, written by Fernando Morais are the main sources that joined by other literary works from Amado and several documents complete the sources for this research. Organized in six parts including the initial and final considerations the whole text is composed by four themes. The first part reflects the representative images about Prestes and Olga in the contemporary age seen by the named Brazilian left and by the couple s daughter Anita Leocadia Prestes. Besides it includes and analyses the several historical interpretations already concluded about the characters. The second, third and fourth approach refer specially to the representations done through the biographies already mentioned. The second approach reflects at first the biographers outlook having the analyzed works as important marcs in the literary life of the writers. Furthermore, the political relevance credited to the texts due to the historical moment of their productions is also studied. Afterwards the limits between history and literature are mentioned checking the details of the biographic gender and its claiming of true narrative that in the case of the approached writers is the expression of a power project. The third theme turns into analyze about memories understanding how the subjective reasons / affectivities are streamlined at the biographies written. Finally we debate identity observing at first place that Amado and Morais hold common similarities within the literary writers and interpreters of the Brazilian national identity and afterwards analyzing the nostalgic elaborations of the characters viewing stimulate the readers to (re)elaborate the image of the identity characteristics of the Brazilian people.